2014
DOI: 10.25011/cim.v37i4.21733
|View full text |Cite
|
Sign up to set email alerts
|

IGF2 expression and β-catenin levels are increased in Frozen Shoulder Syndrome

Abstract: IGF2 expression and β-catenin levels are increased in Frozen Shoulder Syndrome Abstract Purpose: Frozen Shoulder Syndrome is a brosis of the shoulder joint capsule that is clinically associated with Dupuytren's disease, a brosis of the palmar fascia. Little is known about any commonalities in the pathophysiology of these connective tissue broses. β-catenin, a protein that transactivates gene expression, and levels of IGF2 mRNA, encoding insulin-like growth factor-II, are elevated in Dupuytren's disease. e aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 41 publications
(54 reference statements)
1
10
0
1
Order By: Relevance
“…This observation provides a potential molecular link between the two conditions. 35 Raykha et al 36 reported elevated expression of IGF-2 and b-catenin in Dupuytren's disease and adhesive capsulitis.…”
Section: Pathogenesismentioning
confidence: 99%
“…This observation provides a potential molecular link between the two conditions. 35 Raykha et al 36 reported elevated expression of IGF-2 and b-catenin in Dupuytren's disease and adhesive capsulitis.…”
Section: Pathogenesismentioning
confidence: 99%
“… Hagiwara [ 18 ] 2012 case control RI + MGHL + IGHL 12 18 immunohistochemistry, qPCR, scanning acoustic microscopy A higher number of cells, stiffer capsular tissue and increased gene expression related to fibrosis (COL1A1, PDGF-B) inflammation (IL-1β) and chondrogenesis was found Xu [ 19 ] 2012 case control RI 8 10 immunohistochemistry Increased expression of nerve growth factor receptor and new nerve fibers were found in frozen shoulder capsular tissue compared to controls Kim [ 20 ] 2013 case series RI 17 9 immunohistochemistry, RT-PCR ICAM-1 was increased in capsular tissue, synovial fluid, and serum of frozen shoulder patients compared to controls Lho [ 21 ] 2013 case control RI + subacromial bursa 14 7 immunohistochemistry, RT-PCR, ELISA IL-1α, IL-1β, TNF-α, COX-1 and COX-2 were expressed at higher levels in joint capsule of frozen shoulder patients compared to controls. In the subacromial bursa, IL-1α, TNF-α and COX-2 were expressed at higher levels Raykha [ 22 ] 2014 case control + in vitro cell culture RI ? ?…”
Section: Resultsmentioning
confidence: 99%
“…According to the views of modern Western medicine, subacromial bursal tissue inflammation mediated by inflammatory factors [ 8 ] is an important pathological process associated with primary frozen shoulder. As the chronic inflammation develops, fibrotic hyperplasia occurs within the shoulder joint capsule [ 9 ], which affects the articular cavity and joint mobility. In the meantime, calcitonin gene-related peptide (CGRP) and substance P (SP) [ 10 ] in the shoulder joint capsule generate abnormal nerve fibers under the inflammatory immune response, which serves as the pathological basis for intracapsular pain.…”
Section: Discussionmentioning
confidence: 99%